(untitled) (REMUNOM, 2025)
The Lower Tocantins region is one of the regions with great environmental and socioeconomic diversity, making it a subject of study in various fields. This region’s economy is based on agriculture and livestock farming. Despite a considerable percentage of crop cultivation, much of it faces restrictions on crop planting, with areas of medium to high environmental fragility. Therefore, assessing the region’s environmental fragility along with information on agricultural potential is crucial to measuring its agricultural potential, seeking to combine productivity and sustainability. Therefore, the use of geotechnology is one alternative for this type of analysis, which integrates various factors. The study was conducted in the Lower Tocantins region, in the state of Pará, in the Brazilian Amazon, which has 839,022 inhabitants and is made up of 11 municipalities. The objective of this research was to assess the agricultural capacity and environmental susceptibility of the Lower Tocantins microregion. To achieve this, geoprocessing techniques and the integration of components responsible for determining the environmental fragility of a given region were used. The integrated analysis indicates that the Lower Tocantins region faces a dual challenge: although it has significant agricultural potential in certain municipalities, it is also highly vulnerable due to soil, climate, and land use factors.